An Online Survey About Electroconvulsive Therapy in Japan During the COVID-19 Pandemic: Comparison of Early and Recent Stages - Hirata R; Kawashima H; Tsuboi T; Wada K; Takebayashi M; Suwa T (Neuropsychiatric Disease and Treatment, 2022)
Risa Hirata,1 Hirotsugu Kawashima,1,5 Takashi Tsuboi,2,5 Ken Wada,3,5 Minoru Takebayashi,4,5 Taro Suwa1,5 1Department of Psychiatry, Kyoto University Hospital, Kyoto, Japan; 2Department of Neuropsychiatry, Kyorin University School of Medicine, Tokyo, Japan; 3Department of Psychiatry, Hiroshima Citizens Hospital, Hiroshima City Hospital Organization, Hiroshima, Japan; 4Department of Neuropsychiatry, Faculty of Life Sciences, Kumamoto University, Kumamoto, Japan; 5ECT Committee, Japanese Society of General Hospital Psychiatry (JSGHP), Tokyo, JapanCorrespondence: Taro Suwa, Department of Psychiatry, Kyoto University Hospital, 54, Shogoin Kawahara-cho, Sakyo-ku, Kyoto-shi, Kyoto, Japan, Tel +81-75-751-3386, Fax +81-75-751-3246, Email tarosuwa@kuhp.kyoto-u.ac.jpPurpose: To provide an overview of how electroconvulsive therapy (ECT) practice in Japan has changed as the coronavirus disease 2019 (COVID-19) pandemic continues.Patients and Methods: We surveyed healthcare institutions, primarily university and general hospitals, regarding changes in the number of patients undergoing ECT and infection control measures in the early (August 2020) and recent (August 2021) stages of the COVID-19 pandemic. Data for the early and recent stages were also compared between urban and non-urban areas.Results: Among 32 facilities, the number of patients undergoing ECT decreased in 11 facilities (34.4%) from April 2020 to March 2021 compared with the previous year, whereas the number increased in 12 (37.5%) from April to June 2021 compared with the previous year. As of August 2021, some facilities had ongoing restrictions. Compared with non-urban facilities, the number of patients undergoing ECT decreased more in urban facilities, which also had more ECT restrictions. Maintenance ECT was used at the same rate as before the pandemic for 23 (82.1%) of 28 institutions. Regarding infection control measures, many facilities considered polymerase chain reaction testing before ECT and required all staff to wear surgical masks and eye shields during ECT.Conclusion: The COVID-19 pandemic in Japan greatly affected the use of ECT in 2020; however, by the summer of 2021, infection control measures were relatively well established, the number of ECT cases stabilized and increased, and the decision to use ECT was again possible.Keywords: electroconvulsive therapy, coronavirus disease 2019, pandemic, personal protective equipment, clinical decision making